Ghats in Banganga tank - Banganga by Ghosh, Ayan (2023)
Ghats serve multiple purposes, both religious and secular, and is a hub of activity during Hindu festivals like Shivratri, Ganesh Chaturthi and Diwali. Pilgrims use Banganga tank for bathing, to perform suryanamaskar at dawn, and idol immersion. Before piped water was made available in homes, Banganga tank was the main source of drinking water.